Microcredit and Entrepreneurship. Reflections of a lender (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Microcredit is becoming a new system of financing for entrepreneurs, especially in the Third and Fourth Worlds. The aim of this paper is two fold: (1) Reflecting onmicrocredit from the real and practical vision of a lender, and (2) To analyze the new trends emerged from microcredit. In order to achieve these goals, first, we study the relationship of microcredit with informal finance, then, to analyze their economicand social issues from a multidisciplinary perspective. Finally, the new trends in microcredits are described and it is given a decalogue of findings with a practical purpose.
Keywords: Microcredit is becoming a new system of financing for entrepreneurs; especially